Implementation of EMASLIM Leadership in Strengthening Teacher Performance and Professionalism at SATAP Junior High School, Gowa Regency - Lisaw, Irwani; Jumriani, Jumriani; Jumadi, Jumadi (Widyagogik, 2025)
This study aims to describe the implementation of EMASLIM leadership (Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator) as a strategy to strengthen teacher performance and professionalism at SMP SATAP Gowa, which operates in a remote area context. This research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and document analysis involving the principal, teachers, administrative staff, school supervisors, and parents of students. The findings revealed that the principal implemented EMASLIM roles adaptively and integratively through professional guidance utilizing the Merdeka Mengajar Platform (PMM), academic supervision based on a coaching model, resource management aligned with local needs, and the development of a collaborative work culture. Furthermore, the innovation of providing school transportation (mobil tayo) significantly improved student attendance and learning continuity, thereby enhancing teacher motivation, work ethic, pedagogical performance, and professional competence. The implementation of EMASLIM leadership in the context of remote schools proved effective in transforming limitations into opportunities for improving the quality of learning